2018
DOI: 10.1007/s00774-018-0931-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with inadequate responses to risedronate in Japanese patients with osteoporosis

Abstract: Factors associated with an inadequate response (IR) to bisphosphonates have been reported in many countries, but not in Japan, where the approved dose is half the global dose. We analyzed factors associated with IR to risedronate in Japanese patients with osteoporosis. This was a post hoc analysis of 1261 Japanese osteoporosis patients who received risedronate for 1 year in phase III trials. IR was defined as more than one new vertebral fracture (VF) and/or negative change in lumbar spine bone mineral density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…There was not enough statistical power to assess antifracture efficacy in this study ( 294 ). Low baseline BTMs were found to be an independent predictor of inadequate response to risedronate ( 295 ).…”
Section: Part 2 the Use Of Btm In Clinical Practice: Potential Proble...mentioning
confidence: 99%
“…There was not enough statistical power to assess antifracture efficacy in this study ( 294 ). Low baseline BTMs were found to be an independent predictor of inadequate response to risedronate ( 295 ).…”
Section: Part 2 the Use Of Btm In Clinical Practice: Potential Proble...mentioning
confidence: 99%
“…Within the treatment profile features, we were able to include relevant variables which may affect BMD response 14 , 16 , 36 including Age, Sex, Weight, Previous vertebral fractures and pelvis (ICD10-S32*), Fracture of shoulder and upper arm (ICD10-S42*), Fracture of forearm (ICD10-S52*), Fracture of femur (ICD10-S72*), Fracture of lower leg including ankle (ICD10-S82*), Medical history of Gout (ICD10-M10*), Rheumatoid arthritis (ICD10-M051), Essential (primary) hypertension (ICD10-I10), Diabetes mellitus (ICD10-E1*), Disorders of lipoprotein metabolism and other lipidemias (ICD10-E78*), Heart failure (ICD10-I50), and Ischemic heart disease (ICD10-I2). Previous steroid usage history was collected including Budesonide inhaler, Hydrocortisone injection, oral or intravenous Dexamethasone, and oral Prednisolone.…”
Section: Methodsmentioning
confidence: 99%
“…An expert opinion, based on personal experience, found that osteoporotic patients lacking vitamin D have secondary hyperparathyroidism, and that only those with a sufficient level of 25OHD and normal serum PTH levels benefit from good densitometric response to BP [13]. Two recent Japanese studies in more than 1,200 osteoporotic patients treated with risedronate confirm that the densitometric response is better in subjects with vitamin D sufficiency [14,15].…”
Section: Letter To Editormentioning
confidence: 99%